Serum copper and zinc status in obstructive sleep apnea patients [Obstrüktif uyku apneli hastalarda serum baki{dotless}r ve çinko diizeyleri] - (:unkn) unknown (My University, 2013)
Obstructive Sleep Apnea Syndrome (OSAS) is a chronic disease characterized by oxygen desaturation and awakens follow from repetitive apnea and hipopnea during the night. It is thought that diversity of oxygen levels during night in OSAS cause oxidative stress with the increment of the free radical production. In this study, serum levels of copper (Cu) and zinc (Zn), two of the most important elements of antioxidant defense mechanism, were investigated. Patients to be participated into the study were divided into 4 groups according to the result of polysomnography test. Levels of serum Cu and Zn are measured by using flame atomic absorption spectrophotometry equipment. Glucose, blood lipid profile (HDL, LDL, trigliserid, total cholestrol), urea and creatinine were taken into account in all patients. Serum Cu levels were similar with OSAS patients (mild OSAS: I09±37 μg/dL; moderate OSAS: 93±20 μg/dL; severe OSAS: 97±14 μg/dL) and healthy controls (99±37 μg/dL, p>0.05). Serum Zn levels were significantly low in OSAS patients, especially in severe OSAS (mild OSAS: 79±9 μg/dL; moderate OSAS: 79±12 μg/dL; severe OSAS: 74±18 μg/dL) when compared to controls (88±12 μg/dL, p<0.05). These results suggest that patients with severe OSAS are under considerable oxidative stress. Supporting OSAS patients with Zn would be beneficial to decrease oxidative stress and its effects.
Keywords: Cu; Flame atomic absorption spectrophotometry; Obstructive sleep apnea syndrome; Oxidative stress; Zn